Candidate Species for Florida Aquaculture: Discus Symphysodon spp., a Profitable but Challenging Species for Florida Aquaculture - E. J. Livengood; Cortney L. Ohs; Frank A. Chapman (EDIS, 2010)
FA166, an 8-page illustrated fact sheet by E. J. Livengood, C. L. Ohs, and F. A. Chapman, provides an overview of this disc-shaped freshwater chiclid fish — description, habitat and feeding, conservation issues, taxonomy, genetics and domestication, culture methods, and markets. Includes references. Published by the UF Program in Fisheries and Aquatic Sciences, School of Forest Resources and Conservation, December 2009.